2005
DOI: 10.1136/ijgc-00009577-200501000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in theE6gene of human papillomavirus type 16 in the cervical tissues of Korean women

Abstract: The aim of this study was to identify sequence variants in the HPV 16 E6 gene in Korean women and to examine the possible association between these sequence variants and cervical cancer development. We examined the HPV 16 DNA of 215 patients with no cervical disease (NCD) (n = 105) or with cervical neoplasia (n = 110) [cervical intraepithelial neoplasia (CIN), n = 61; invasive cervical carcinoma (ICC), n = 49] using the nested polymerase chain reaction (PCR) and PCR-directed sequencing methods. Fifty-four (NCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…In the study, they detected a change of nucleotide affecting the predicted amino acid related with antigenicity and biding to retinoblastoma protein. However, in two other more recent studies targeting Korean women, there was no significant correlation between specific HPV 16 variants and severity of cervical lesions 23,24 . In the present study, HPV 16 variants E6 T178G and E7 A647G were the most prevalent in Korean women and showed statistically significant association with the severity of cervical neoplasia ( P trend = 0.0002, P < 0.0001; P trend < 0.0001, P < 0.0001, respectively).…”
Section: Discussioncontrasting
confidence: 69%
“…In the study, they detected a change of nucleotide affecting the predicted amino acid related with antigenicity and biding to retinoblastoma protein. However, in two other more recent studies targeting Korean women, there was no significant correlation between specific HPV 16 variants and severity of cervical lesions 23,24 . In the present study, HPV 16 variants E6 T178G and E7 A647G were the most prevalent in Korean women and showed statistically significant association with the severity of cervical neoplasia ( P trend = 0.0002, P < 0.0001; P trend < 0.0001, P < 0.0001, respectively).…”
Section: Discussioncontrasting
confidence: 69%
“…Dashes indicate no variation. As ---C ------E378D 1 0?76 As -------G --K382E 1 0?76 A f 1 ---------a 1 0 ?76 AA/Af2 ----C ----a T379P 1 0?76 n 1 1 1 1 1 2 1 1 1 2 1 3 1 in Korean women (Kang et al, 2005). A previous report showed that other variations in E6 (E/G131T) result in amino acid changes in potential T-cell receptor-or HLAbinding regions (Ellis et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…This variant leads to an amino acid change at residue 83 from a leucine to a valine (denoted L83V) and may increase the pathogenicity of HPV16 by enhancing persistency of infection in cervical cancer, 29,30 although the results are still controversial. [31][32][33] In HNSCC, T350G is the most prevalent E6 genomic variant and has a higher viral load compared with the prototype. 34,35 In contrast, the E7 genetic sequence is widely conserved in cervical cancer, as demonstrated in a cohort of 5570 HPV16infected cases.…”
Section: The True Impact Of Hpv On Head and Neck Cancer Hpv Infectionmentioning
confidence: 99%